The Constitutional Court’s Protection and Fulfilment of the Citizens’ Rights: Constitutional and Islamic Law Perspectives - A. Gani, Iskandar; Asmara, Romi; Sulaiman, Sulaiman; Husna, Asmaul (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This study aims to examine the degree to which the Constitutional Rights of Indonesian Citizens are maintained by the state, specifically focusing on democratic Public Elections (Pemilu) and Public Elections for Regional Heads (Pemilukada). This study centers on the advancement of the political democratic process, particularly concerning law enforcement and the safeguarding of human rights. This analysis focuses on the implementation of these features by the Constitutional Court (Mahkamah Konstitusi), which has the responsibility of handling post-conflict public election issues. This study utilizes empirical legal methodologies, employing a framework that combines the constitutional law and the Islamic law. The data was acquired through in-depth interviews and a meticulous examination of pertinent literature. The participants were experts in the domains of the constitutional law and the Islamic law. This paper argues that the state has successfully protected the legal rights of citizens by incorporating them into laws, so fulfilling their constitutional privileges. Constitutional rights refer to essential human rights, particularly the right to engage in the democratic process through voting or candidacy in public elections. In the Indonesian state administration system, citizens have the privilege to report any election matters to the appropriate authorities and have it lawfully resolved by the Constitutional Court Institution. The Islamic law supports the harmonization of law enforcement and the protection of citizens' rights within the context of human rights. In Aceh, a region that implements special autonomy and the Islamic law, there is no prejudice against the rights of individuals based on their gender or religion. Under the Islamic law, voting or running for office is regarded as a right rather than an obligation. However, participating in the act of voting is highly valued as it provides benefits and serves as a preventive measure against damage.